Optimal Income Distribution Rules and Representative Consumers - Jerison, M. (Review of Economic Studies, 1994)
This paper derives observable properties of economies with optimal income distribution rules that specify consumers' incomes as functions of aggregate income and prices. Optimality implies that the aggregate demand function is generated by a single “representative” consumer, cf. Samuelson (1956). We derive an additional implication which, when consumers receive fixed shares of aggregate income, requires that the consumers' demands become more dispersed when aggregate income rises. This last condition has empirical support. The results relate the representative consumer's preferences to a version of Kaldor's compensation criterion and show when both can be used for normative analysis without internal inconsistency.